Motor threshold predicts working memory performance in healthy humans. (6th December 2013) - Schicktanz, Nathalie; Schwegler, Kyrill; Fastenrath, Matthias; Spalek, Klara; Milnik, Annette; Papassotiropoulos, Andreas; Nyffeler, Thomas; de, Dominique J.‐F.
Abstract Cognitive functions, such as working memory, depend on neuronal excitability in a distributed network of cortical regions. It is not known, however, if interindividual differences in cortical excitability are related to differences in working memory performance. In the present transcranial magnetic stimulation study, which included 188 healthy young subjects, we show that participants with lower resting motor threshold, which is related to higher corticospinal excitability, had increased 2‐back working memory performance. The findings may help to better understand the link between cortical excitability and cognitive functions and may also have important clinical implications with regard to conditions of altered cortical excitability.